Analisis Kebijakan Pemerintah Kabupaten Klaten terhadap Pemenuhan Hak Penyandang Disabilitas dalam Bidang Pelayanan Publik - Ekklesia Abdi Prayoga Prayoga; Sunny Ummul Firdaus (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis research analyzes existing policies in Klaten Regency related to the fulfillment of the rights of persons with disabilities in the field of public services. Human rights are rights that are inherently inherent in every human life. The state is obliged to guarantee these rights by using legislation as a means of protection. The District Government of Klaten which carries out the autonomy function is obliged to carry out regulations which are indeed its duties and responsibilities. There are 4 regulations relating to the delivery of public services for persons with disabilities. These regulations have fulfilled the principles of the formation of laws and regulations in substance, but there are orders that have not been implemented yet by regents, namely regulations that regulate public services for persons with disabilities themselves, so there is a legal vacuum.Keywords : rights; persons with disabilities; public services.